Using remote consultation to enhance diagnostic accuracy of bedside transthoracic echocardiography during COVID‐19 pandemic. Issue 8 (31st May 2021) - Lu, Jing; Lin, Jun; Yin, Lixue; Shi, Rui; Li, Huanxing; Ge, Yang; Luo, Jing
Abstract: Objective: The aim of this study was to evaluate the clinical significance of remote consultation over bedside transthoracic echocardiography (RC‐B‐TTE) for patients with coronavirus disease 2019 (COVID‐19). Methods: Five frontline echocardiographers performed and interpreted B‐TTE for 30 patients with COVID‐19 in the isolation wards, and the on‐site B‐TTE reports (OSR) were generated. Then remote consultation over the 30 B‐TTE studies was conducted by two experienced echocardiographic consultants while blinded to the OSR, and the corresponding remote consultation reports (RCR) were generated. Subsequently, the five frontline echocardiographers were convened together to discuss the difference between the OSR and RCR, and to confirm the correct interpretation and the misdiagnosis using a "majority‐vote" consensus as the diagnostic "gold standard". Afterwards the reasons for the misdiagnosis were given by the frontline echocardiographers themselves. The inter‐rater agreement between the OSR and the "gold standard" was assessed using Kappa coefficient and percent agreement. Results: Complete correctness of the 30 copies of the RCR were determined by the 5 frontline echocardiographers. The reliability of the OSR in the findings of cardiac chamber dilation, left ventricular hypertrophy and pulmonary hypertension were weak ( Kappa <0.6). The reliability of the OSR in the recognition of major cardiac abnormalities was very weak ( Kappa =0.304, percent agreement =63.3%). Misdiagnosis of major abnormalities was found in 11 copies of OSR (11/30, 36.7%). Conclusions: The protocol of RC‐B‐TTE has shown noticeable superiority in ameliorating diagnostic accuracy of echocardiography, which should be generalized to clinical practice during the COVID‐19 or similar pandemic.